A RETROSPECTIVE ANALYSIS OF CALCINOSIS CUTIS: A COMMON ENTITY AT UNCOMMON ANATOMICAL SITES. - Mehra, Pallavi; Aditi, Sneha; Prasad, Krishna Murari; Kumar, Dilip (Student’s Journal of Health Research Africa, 2024)
Background Calcinosis cutis can be defined as a condition of calcium salts deposition on the surface of the skin including the deepest layer called hypodermis. Many interesting medical data about calcinosis cutis are available in pathological and clinical literature. This condition can be subdivided into five types, they are dystrophic, metastatic, idiopathic, iatrogenic, and calciphylaxis. Among these types, dystrophic calcification is the major cause and it is interlinked with the levels of phosphorus and calcium. Objective This study aims to spotlight the numerous clinical and pathological characteristics of calcinosis cutis from various lesions in medical history. Methods A complete investigation of the clinical and pathological characteristics of calcinosis cutis in all the selected cases was performed. The type of the study was retro-prospective where the data of seven years i.e. from July 2016 to June 2023 were collected from the Department of Pathology, PMCH, and Patna. Results A total of 17 cases with the condition of calcinosis cutis were selected for the study. Among these, the sites of the lesion were different (from 1 mm to 5 cm) in measurements and location in a few patients. The scrotum was the common location of the lesion. The selection of treatment was “wide surgical excision”. The histopathological treatment was hardly challenging. Conclusion This study showcased various measurements and locations of the lesions site of the histopathological construction, and therefore this study spotlights the numerous clinical and pathological characteristics of calcinosis cutis from various lesions.